Analisis Perkembangan Bahasa pada Anak Usia Dini - Nurhaliza Nurhaliza; Lola Via; Mutiara Hoiroh; Elda Azahra; Sry Apfani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Language is the primary tool of communication used by humans to express intentions and goals. In the context of early childhood development, language skills play a crucial role in supporting children's social, cognitive, and emotional interactions. One common issue that arises is speech delay, a condition in which a child experiences obstacles in various aspects of language, including articulation, voice, fluency, and sound comprehension. This article aims to theoretically examine language development in early childhood with speech delay, focusing on the aspect of receptive language. Data were obtained through a literature review of various relevant journals and theses. The results of the study indicate that both internal factors (such as neurological conditions) and external factors (especially parenting patterns) influence speech delays. Children with mild speech delay can show progress through proper stimulation, while those with more severe conditions require professional intervention.